2015
DOI: 10.1007/s10557-015-6629-y
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Receptor Activator Maxacalcitol Provides Cardioprotective Effects in Diabetes Mellitus

Abstract: Our results suggest that OCT prevents the development of cardiac damage in DM, independent of RAS inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Many studies have shown that oxidative stress may contribute to the pathogenesis of VC progression in a rat CKD and DM model 28,29 . Our several previous studies also proved that an increase in oxidative stress was associated with the progression of kidney and cardiovascular injury in not only CKD but also DM [16][17][18]30 . In this study, both the CKD and DM groups manifested increased oxidative stress and rats with CKD complicated by DM exhibited increased oxidative stress compared with them.…”
Section: Discussionmentioning
confidence: 61%
“…Many studies have shown that oxidative stress may contribute to the pathogenesis of VC progression in a rat CKD and DM model 28,29 . Our several previous studies also proved that an increase in oxidative stress was associated with the progression of kidney and cardiovascular injury in not only CKD but also DM [16][17][18]30 . In this study, both the CKD and DM groups manifested increased oxidative stress and rats with CKD complicated by DM exhibited increased oxidative stress compared with them.…”
Section: Discussionmentioning
confidence: 61%
“…2MD is another novel and potent VDRA that has a wider therapeutic margin in the uremic rat model than calcitriol or paricalcitol, and suppresses PTH without hypercalcemia in HD patients [ 163 ]. A recent study showed that maxacalcitol can prevent the development of cardiac damage in DN rats, independent of RAS inhibition [ 164 ]. However, a pooled analysis revealed that there are no differences on the efficacy and safety between paricalcitol and other VDRAs for treating dialysis patients [ 165 ].…”
Section: Therapeutic Effects Of Vdr Activationmentioning
confidence: 99%
“…Further, decreased cardiac fibrosis [11] and attenuated cardiac remodeling and dysfunction in polycystic ovarian syndrome [70] with vitamin D supplementation and/or VDR activation suggest the role of vitamin D in treating cardiac fibrosis [71]. Furthermore, the cardioprotective effects of VDR activators and modulators suggest the potential therapeutic role of vitamin D [7273]. …”
Section: Cardiac Diseasesmentioning
confidence: 99%